KUALITAS PELAYANAN KESEHATAN MASYARAKAT DI PUKESMAS - E.21111102, Jilawati (FISIP Universitas Tanjungpura, 2013)
The problem in this study is still found no place officers at work, as well as health facilities are still limited sanggat. The purpose of this study is to want to examine and describe the public health service, namely the quality of medical personnel in providing care for patients who are in great Sajingan Sambas district health centers. The results showed that the public health services in District Health Clinics Sajingan Besar has not done well, it's based on research that shows a simple service and condition of health facilities, assessed by the informant can not be executed properly. To address this phenomenon the authors suggest should be increased by providing explanations to patients who seek treatment are more details on the services that are easy on the PHC Sajingan Great Sambas district still needs to be improved about the doctor in charge should always working hours so that the patient or the public do not wait longer and get direct care of a physician. PHC facilities in Great Sajingan Sambas district still need to be completed such as medical supplies, waiting benches, fans, the parking lot in order to facilitate and provide comfort in the service process. It is expected the officers of service providers (doctors and nurses) in order to improve the quality of health services to the community by approaching people or patients. Keywords: Quality of Care, Public Health, Facilities and Services Easya